Design and fabrication of helical antennas with non-uniform cross-section wire via metal additive manufacturing - Martins, Nícholas Fonseca [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
This dissertation presents a study on helical antennas, introducing a new mathematical formulation for representing the helix, in which the diameter, spacing, and cross-section of the metal wire are non-uniform. It is demonstrated how these modifications, combined with optimization techniques, can be used to improve the electromagnetic performance of designed antennas. Precisely defining the transition region between the helix and the central feeding point, a thicker wire was strategically employed at the base to enhance both the antenna’s operational bandwidth and mechanical strength, eliminating the need for additional support structures. The wire diameter was linearly reduced towards the top of the helix to improve radiation characteristics. To address the manufacturing challenges presented by the complex geometries of non-uniform helical antennas, the additive metal manufacturing process was employed. Maraging steel was chosen for its ability to withstand severe environmental conditions and temperature fluctuations without experiencing significant deformations, distinguishing it from polymer alternatives. The proposed formulation was explored using three models tailored for the X-band (8 GHz to 12 GHz): Model I) A standard helical antenna featuring uniform diameter and helix spacing; Model II) a helical antenna with non-uniform diameter and helix spacing; and Model III) a helical antenna with non-uniform diameter, cross-section, and helix spacing. The findings illustrate that the helical antenna utilizing a tapered cross-section wire (thicker at the base and thinner at the tip) exhibits significantly superior performance compared to the control models. Specifically, we present an eight-turn helical antenna that attained a measured reflection coefficient below −10dB and an axial ratio of less than 1dB across the X-band, with a peak realized gain in right-hand circular polarization (RHCP) of 10.8dBic.

Esta dissertação apresenta um estudo sobre antenas helicoidais, introduzindo uma nova formulação matemática para a representação da hélice, no qual o diâmetro, espaçamento e seção transversal do fio metálico não são uniformes. É demonstrado como essas modificações, combinadas à técnicas de otimização, pode ser utilizadas para melhorar o desempenho eletromagnético das antenas projetadas. Definindo de forma precisa a região de transição entre a hélice e o ponto de alimentação central, um fio mais grosso foi estrategicamente empregado na base para aprimorar tanto a largura de banda operacional da antena quanto a resistência mecânica, eliminando a necessidade de estruturas de suporte adicionais. O diâmetro do fio foi linearmente reduzido até o topo da hélice para melhorar as características de radiação. Para lidar com os desafios de fabricação apresentados pelas geometrias complexas das antenas helicoidais não uniformes foi utilizado o processo de manufatura aditiva de metais. Foi escolhido aço Maraging por apresentar a suporte condições ambientais severas e flutuações de temperatura sem experimentar deformações significativas, distinguindo-a das alternativas de polímeros. A formulação proposta foi explorada usando três modelos projetados para a banda X (8 GHz a 12 GHz): Modelo I) Uma antena helicoidal padrão apresentando diâmetro e espaçamento das hélices uniformes; Modelo II) uma antena helicoidal com diâmetro e espaçamento das hélices não uniformes; e Modelo III) uma antena helicoidal com diâmetro, seção transversal e espaçamento das hélices não uniformes. Os resultados mostram que a antena helicoidal utilizando um fio de seção transversal cônica (mais grosso na base e mais fino na ponta) exibe desempenho significativamente superior em comparação com os modelos de controle. Especificamente, apresentamos uma antena helicoidal de oito voltas que alcançou um coeficiente de reflexão medido abaixo de −10 dB e uma razão axial de menos de 1 dB em toda a banda X, com um ganho máximo realizado em polarização circular à direita (RHCP) de 10.8 dBic.
Design e fabricação de antenas helicoidais com fio de secção transversal não uniforme através de manufatura aditiva de metal
Keywords: Antennas (Electronics); Microwave antennas; Microwave communication systems